Simulink model of transformer differential protection using phase angle difference based algorithm - NA Iqteit, K Yahya (IAES Institute of Advanced Engineering and Science, 2020)
Simulink model of transformer differential protection using phase angle difference based algorithm
Keywords: Differential relay Inrush current Internal fault Phase angle difference